Multiplicity dependence of charged-particle production in pp, p–Pb, Xe–Xe and Pb–Pb collisions at the LHC - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (Elsevier, 2023)
Multiplicity (Nch) distributions and transverse momentum (pT) spectra of inclusive primary charged particles in the kinematic range of |η| < 0.8 and 0.15 GeV/c < pT < 10 GeV/c are reported for pp, p–Pb, Xe–Xe and Pb–Pb collisions at centre-of-mass energies per nucleon pair ranging from √sNN = 2.76 TeV up to 13 TeV. A sequential two-dimensional unfolding procedure is used to extract the correlation between the transverse momentum of primary charged particles and the charged-particle multiplicity of the corresponding collision. This correlation sharply characterises important features of the final state of a collision and, therefore, can be used as a stringent test of theoretical models. The multiplicity distributions as well as the mean and standard deviation derived from the pT spectra are compared to state-of-the-art model predictions. Providing these fundamental observables of bulk particle production consistently across a wide range of collision energies and system sizes can serve as an important input for tuning Monte Carlo event generators
Keywords: Multiplicity (mathematics); Physics; Charged particle; Nuclear physics; Large Hadron Collider; Spectral line; Monte Carlo method; Impact parameter; Observable; Atomic physics; Ion; Geometry; Statistics; https://purl.org/pe-repo/ocde/ford#1.03.04